Electronic teaching aid for biomedical engineering course - Afiq Husaini Khairudin, 1994- , author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Kejuruteraan (Bio-Perubatan)) - Universiti Teknologi Malaysia, 2017